ApoA-I/HDL Generation and Intracellular Cholesterol Transport through Cytosolic Lipid-Protein Particles in Astrocytes. (12th August 2014) - Ito, Jinichi; Michikawa, Makoto
Abstract : Exogenous apolipoprotein A-I (apoA-I) associates with ATP-binding cassette transporter A1 (ABCA1) on the cell surface of astrocytes like various peripheral cells and enhances the translocation of newly synthesized cholesterol from the endoplasmic reticulum/Golgi apparatus (ER/Golgi) to the cytosol. The cholesterol translocated to the cytosol is incorporated to cytosolic lipid-protein particles (CLPP) together with phospholipids and proteins such as sphingomyelin, phosphatidylcholine, caveolin-1, protein kinase C α (PK-C α ), and cyclophilin A. The CLPP are high density lipoproteins- (HDL-)like cytosolic lipid-protein complex with densities of 1.09–1.16 g/mL and diameters of 17-18 nm. The association of exogenous apoA-I with cellular ABCA1 induces tyrosine phosphorylation, activation, and translocation to the CLPP of ABCA1-associated phospholipase C γ (PL-C γ ) in rat astrocytes. Furthermore, PK-C α is translocated and activated to/in the CLPP through the　production of diacylglyceride in the CLPP. ApoA-I enhances both the association of CLPP with microtubules and the phosphorylation of α -tubulin as a component of microtubules. The CLPP are dissociated from microtubules after α -tubulin in microtubules is phosphorylated by the CLPP-associated PK-C α . The association and dissociation between CLPP and microtubules may participate in the intracellular transport of cholesterol to the plasma membrane.